The Role of Augmented Reality in Interactive Mobile Learning Current Trends and Future Directions - Rahman, Ayesha; Haque, Md Rezwanul (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2025)
This study systematically reviews 93 empirical studies published between 2015 and 2024 to examine the role of Augmented Reality (AR) in interactive mobile learning, with particular attention to its applicability in Bangladesh’s educational context. The findings reveal that mobile AR significantly improves student engagement, learning achievement, and motivation across various disciplines and educational levels. AR proves especially effective in fields requiring spatial reasoning such as science, mathematics, and language learning. It also supports inclusive education by helping learners with autism and dyslexia through adaptive visual learning environments. However, challenges remain, including inadequate teacher readiness, limited professional development, and infrastructure constraints, particularly in rural regions. The study concludes that AR offers strong potential to advance interactive learning and educational equity in developing countries, but its success depends on contextually grounded strategies, teacher training, technical support, and institutional commitment to long-term integration.